2014
DOI: 10.1093/rheumatology/keu258
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in polymyositis and dermatomyositis complicated by rapidly progressive or chronic interstitial lung disease

Abstract: IL-6, IL-8, TNF-α and IP-10 are associated with global disease activity in PM/DM. These cytokine levels were high, especially in the ILD subset. Serum IL-8 levels and the balance between IL-4 and IFN-γ may contribute to the differences in pathophysiology between anti-ARS-ILD and anti-MDA5-ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
120
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 29 publications
12
120
3
3
Order By: Relevance
“…These cells produce leukotriene B4 and IL-8 in response to high serum IL-18 concentration and stimulate neutrophils to induce lung fibrosis. [22][23][24] Previous study in mice demonstrated that IL-2 and IL-18 were responsible for the induction of ILD via …”
Section: Discussionmentioning
confidence: 99%
“…These cells produce leukotriene B4 and IL-8 in response to high serum IL-18 concentration and stimulate neutrophils to induce lung fibrosis. [22][23][24] Previous study in mice demonstrated that IL-2 and IL-18 were responsible for the induction of ILD via …”
Section: Discussionmentioning
confidence: 99%
“…60,61 These serological characteristics may indicate the activation of monocytes and macrophages in the pathophysiology of anti-MDA5-positive DM with intractable ILD, although other cytokines, such as IL-8, IL-10 and interferon-a are also elevated, suggesting complex mechanisms in the pathophysiology of the disease. [61][62][63] HRCT findings of anti-MDA5-positive patients were reported by Tanizawa et al as an absence of intralobular reticular opacities and a predominance of consolidation and GGO in lower lung fields or random GGO patterns. 37 Because of the very poor prognosis of DM patients who develop RP-ILD, combined immunosuppressive therapy has been recommended.…”
Section: Anti-mda5 Antibodymentioning
confidence: 99%
“…Research of cytokine profiles demonstrated that serum IL8 level was significantly higher in polymyositis/ dermatomyositis patients with anti-melanoma differentiationassociated gene 5 (anti-MDA5) antibody-associated ILD [8].…”
Section: Introductionmentioning
confidence: 99%